The Effectiveness of the Supervision in Preventing Irregularities in State Finances Management Implementation by the East Java Regional Police
State finance as an instrument of economic policy for the government has a very central role in the administration of the state. Unfortunately, the management of state finance has not been matched with optimal oversight. As the result, there are many cases of misappropriation of the management of state finances. One of the example is related to a village fund corruption case. Village funds are funds sourced from the APBN that are transferred through the APBD and in the form of the APBDes. In its implementation, there are many vilages funds that have not been used optimally and in accordance with its planning. Referring to these problems, the problem of this paper is 1